The genome assembly of the farmed European whitefish Coregonus lavaretus L. from the Finnish selective breeding programme - Kisun Pokharel; Daniel Fischer; Terhi Iso-Touru; Ilma Tapio; Miika Tapio; Tuomas Leinonen; Antti Kause (BMC Genomic Data)
Abstract Objectives European whitefish (Coregonus lavaretus L.) is a freshwater salmonid that inhabits cold regions of central and north Europe and Siberia. It is an important aquaculture species in Finland, selectively bred since 1999. The breeding programme has applied genomic selection that uses SNP markers and phenotypic data to improve traits such as growth, product quality, and fish health. Salmonids are known for chromosomal rearrangements, and the current C. lavaretus reference genome that is based on an individual from Switzerland may deviate from the Finnish one. Therefore, we have assembled a genome for the Finnish European whitefish. This allows us to better assess the genetic basis of fish traits and to enhance the accuracy of genomic selection. Data description The genome of European whitefish was sequenced using a combination of Illumina and PacBio technologies and assembled using wtbg2 and HiRise software. The assembly has a size of 2.94 Gb and comprises 6,706 scaffolds with the scaffold N50 of 1.36 Mb.